Growth and milk production performance of Abergelle goats under the community-based breeding program in northern Ethiopia - Walle, Yeshiwas; Wondim, Bekahagn; Gobeze, Mulatu; Aklog, Wubeneh; Getachew, Tesfaye; Demilie, Alemu; Tesema, Zeleke (Ethiopian Journal of Science and Technology, 2025)
Community-based goat breeding program (CBBP) is becoming an alternative genetic improvement approach for low input production system and being implemented nationwide in Ethiopia. A community-based breeding program was implemented in Abergelle goat breed for six years (2014-2019) at Bilaque village in Ziquala district, Wag-himra zone of North Eastern Ethiopia. The objective of the study was to evaluate the growth and milk production performance of Abergelle goats under community-based genetic improvement program. Best bucks were selected on a yearly basis based on their estimated breeding value and unselected bucks were culled out from the population through castration and sale. Body weight of kids and does milk yield data were collected from flock in the community-based breeding program. A general linear model procedure of SAS was used for data analysis. Birth type, year of birth, and parity had significant (p<0.05) effects on the pre-weaning growth performance of Abergelle goats. The mean yearling weight of kids had slightly increased from 12.8±0.11 to 13.7±0.12 kg during the course of four round selections. Daily milk yield was significantly (p<0.05) affected by the season of lactation and years. Average daily milk yield has increased from 300.31±7.41 ml to 352.62±14.33 ml during the selection years. Death (22%), sale (44%), share (5.5%), and slaughtering (8%) were the major off-take reasons in the flock. The study gave some insight into the possibility of improvement of growth and milk production traits through strategic design and implementation of community-based selective breeding approaches. This approach can suit the existing management level and breeding practices of farmers and it can allow the use of elite bucks and the removal of inferior ones from the population.